OsLUGL is involved in the regulating auxin level and OsARFs expression in rice (Oryza sativa L.). (November 2019) - Yang, Chunyan; Liu, Xi; Li, Dianli; Zhu, Xingjie; Wei, Ziyao; Feng, Zhiming; Zhang, Long; He, Jun; Mou, Changling; Jiang, Ling; Wan, Jianmin
Highlights: Mutation of OsLUGL can cause uncharacteristic floret and abnormal seed in rice. OsLUGL-OsSEU-OsAP1-OsSEP3 functions together as a transcription co-regulator to regulate A/B/C/D/E genes expression during floral development. OsAP1 and OsSEP3 regulate OsGH3-8 expression through binding to promoter of OsGH3-8 . The altered of OsGH3-8 can lead to a change of IAA content, which further effect the expressions of OsARFs . OsLUGL involved in regulating of floral development through auxin related process. Abstract: Specification of floral organ identity is critical for floral morphology and inflorescence architecture. Floral organ identity in plants is controlled by floral homeotic A/B/C/D/E-class genes. Although multiple genes regulate floral organogenesis, our understanding of the regulatory network remains fragmentary. Here, we characterized a rice floral organ gene KAIKOUXIAO ( KKX ), mutation of which produces an uncharacteristic open hull, abnormal seed and semi-sterility. KKX encodes a putative LEUNIG-like (LUGL) transcriptional regulator OsLUGL . OsLUGL is preferentially expressed in young panicles and its protein can interact with OsSEU, which functions were reported as an adaptor for LEUNIG. OsLUGL-OsSEU functions together as a transcriptional co-regulatory complex to control organ identity. SEP3 (such as OsMADS8) and AP1 (such as OsMADS18) serve as the DNA-binding partner of OsLUGL-OsSEU complex. Further studies indicated that OsMADS8 and OsMADS18 could bind to the promoter of OsGH3-8 . The altered expression of OsGH3-8 might cause the increased auxin level and the decreased expression of OsARFs . Overall, our results demonstrate a possible pathway whereby OsLUGL-OsSEU-OsAP1-OsSEP3 complex as a transcriptional co-regulator by targeting the promoter of OsGH3-8, then affecting auxin level, OsARFs expression and thereby influencing floral development. These findings provide a valuable insight into the molecular functions of OsLUGL in rice floral development.